From Digital (Art) Curation to Networked Co-Curating - Dekker, Annet (Mimesis Journal, 2024)
The article combines personal experiences, collaborative projects, and critical analyses to explore the evolving landscape of cultural heritage in the digital realm. Emphasizing the interplay among digital curation, digital art curation, and networked co-curating, it examines three art projects and addresses key considerations, including technology’s impact on digital heritage, the evolving role of users in co-curating, and narrative exploration of historical events in the digital space. Through these examples, the article provides insights into the transformation of cultural heritage practices online, encapsulated in the dynamic interrelationship between humans and technology.